Education futures for school leadership : evidence-informed strategies for managing change - Couture, Jean-Claude, 1955-; Murgatroyd, Stephen J. (New York, NY : Routledge, 2025)
"Education Futures for School Leadership is a comprehensive resource to support school leaders as they encounter the growing complexity and uncertainties that characterize life in schools today. Moving beyond conventional change management literature, this book invites current and aspiring school leaders to apply the interdisciplinary tools of futures studies and strategic foresight to their work. Given our shared global challenges, young people deserve schools that are agile, adaptive, and responsive to many possible futures. Driven by the imperatives of equity and inclusion, the authors provide practical, evidence-informed strategies, real-world examples, and use cases of futures thinking applied to school staff development and change strategies. Each chapter engages with key educational realities: differentiating instructional planning and assessment, the impacts of artificial intelligence and other technologies, the growing psycho-social issues young people are facing, and more. Informed by years of international collaboration with forward-thinking school leaders and scholars, this book is both a field guide and a call to action for navigating the influence of the future on our present moment and the challenges and promises shaping school life today"--
School leaders and futures thinking -- Seeing the future through narrative -- Futures studies and the discipline of anticipation -- Navigating reimagined educational futures -- Adaptive school cultures for our VACU world -- Making the futures present : making a time-shift happen -- Leadership of anticipation in the digital disruptions of education -- Scenarios for the future of schools -- Regenerative thinking as a futures tool -- Building capabilities for the future : the coaching work of school leaders -- Epilogue : a letter to our readers from 2030.
Keywords: School management and organization; Educational leadership; Education -- Forecasting; EDUCATION / Leadership; EDUCATION / Aims & Objectives